Soluble Markers of Antibody Secreting Cell Function as Predictors of Infection Risk in Rheumatoid Arthritis. (28th April 2019) - Gutierrez, Maria J.; Desiderio, Stephen V.; Wang, Nae-Yuh; Darrah, Erika; Cappelli, Laura; Nino, Gustavo; Jones, Michelle; Bingham, Clifton O.
Abstract : Background . Rheumatoid arthritis (RA) is a systemic autoimmune disease associated with immune dysregulation and increased risk of infections. The presence of autoantibodies and immunoglobulin abnormalities indicates B-cell and antibody-secreting cell (ASC) dysfunction. We hypothesize that soluble factors associated with B-cell and ASC activity are decreased in RA patients and that this is linked to higher susceptibility to infections. Methods . Using the Johns Hopkins Arthritis Cohort and Biorepository, we contrasted serum protein levels of soluble factors involved in B-cell activation (CD40, CD40L) and B-cell/ASC homing (CXCL10, CXCL11, and CXCL13) or survival (BAFF, APRIL, TACI, and BCMA) in 10 healthy subjects and 23 adult RA patients (aged 24-65 years). We subdivided RA patients into those with (n = 17 ) and those without infections (n = 6 ) within a 2-year period. In order to reduce the effect of RA treatment, we only included patients receiving methotrexate monotherapy or no RA treatments at baseline. Soluble serum protein levels of B-cell/ASC factors were quantified by multiplex immunoassays. Results . We identified that (1) serum levels of soluble BCMA, APRIL, CD40, and CD40L were significantly decreased in RA patients relative to healthy individuals; (2) serum soluble BCMA, predominantly released by ASC, correlated with serum concentrations of class-switched immunoglobulins, IgG and IgA; and (3) RA patients with a history of infections had significantly lower soluble BCMA levels compared with healthy donors and with RA patients without infections. Conclusions . Our study using soluble factors linked to B-cell/ASC activation and survival suggests that there is a paucity of ASC in a subset of RA patients and that this may be linked to altered antibody production and increased risk of infections. Further delineating the link between ASC and infection susceptibility in RA may optimize disease management and provide novel insights into disease pathogenesis that are susceptible to intervention.